Những yếu tố ảnh hưởng đến ý định sử dụng thanh toán di động trong thời đại số hóa của người dân tại Việt Nam. - Nguyễn Ngọc, Dung; Hoàng Thị Tuyết, Nhung; Nguyễn Thị Ánh, Nhung; Phạm Tô Thục, Hân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
On the basis of the Unified Theory of Acceptance and the Use of Technology, the technology acceptance model and the Theory of Planned Behavior, this study explores a comprehensive picture of the relationship between external and belief factors, which eventually affects intention to use mobile payment of inhabitants. Additionally, this relation is also considered based on 2 types of mobile payment users: Early and late adopters. The study is conducted in two phases: Qualitative and quantitative, and considered the concordance by the Structural Equation Modeling (SEM). The results obtained from data collected from 300 users, affirming that there are positive relationships among the external elements of Mobility, Reachability, Compatibility, Convenience, Innovativeness, M-payment knowledge to belief elements (Perceived Usefulness, Perceived Ease of Use), which ultimately lead to a constructive impact on the Intention to use mobile payment, as well as proving the positive relationship between the Perceived Ease of Use and Perceived Usefulness.